Why Grimilde deserves a happy ending. Narrative complexity of the “villains” in audiovisual fairy tales - Casoli, Sara (E|C, 2020)
The equation "antagonist = villain" is a convention institutionalized by a narrative and representative practice, which new audiovisual products are putting in crisis: the villain, therefore, can become the protagonist, or at least co-protagonist. In this passage, a key role will be played by the adoption of the serial narrative form, able to ensure that the viewer, overcoming his own preconceptions, is able to grant benevolence to those "bad guys" traditionally rejected, and to ensure that even for Grimilde, Snow White's nasty nemesis, seems right to reserve a happy ending.